2024
DOI: 10.1186/s12903-023-03791-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of photodynamic therapy for oral leukoplakia: a retrospective study of 50 patients

Yanting Wang,
Haonan Tang,
Keyi Wang
et al.

Abstract: Background Topical photodynamic therapy (PDT) has demonstrated encouraging results in the treatment of oral leukoplakia (OLK). However, data on the clinical efficacy of PDT in Chinese patients with OLK are still limited. Methods Fifty patients diagnosed with OLK were enrolled, including patients with various dysplastic tissues. All patients received topical PDT with 5-aminolevulinic acid (5-ALA) as a photosensitizer. Clinical efficacy was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous studies in an in vitro setting suggested that human neoplastic cellular growth has been inhibited by the usage of lycopene [ 27 ]. Surgical excision remains one of the most common treatment modalities for oral leukoplakia and includes conventional surgery, cryosurgery, laser excision, and electrocoagulation [ 6 ]. This was concordant with the results of the present study and surgical excision was predominantly performed for patients with oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in an in vitro setting suggested that human neoplastic cellular growth has been inhibited by the usage of lycopene [ 27 ]. Surgical excision remains one of the most common treatment modalities for oral leukoplakia and includes conventional surgery, cryosurgery, laser excision, and electrocoagulation [ 6 ]. This was concordant with the results of the present study and surgical excision was predominantly performed for patients with oral leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of leukoplakia remains an enigma. Previous studies have proposed that the pathogenesis of leukoplakia is driven by somatic genetic mutations that affect the growth, survival, and cycle control of keratinocytes, reflecting as hyperkeratosis, hyperplasia, and dysplasia histopathologically, which translates clinically as changes in color and texture of the mucosa [ 6 ]. Genetic alterations in various oncogene drivers such as EGFR , MYC , CCND1 , and CDKN2A have been found.…”
Section: Introductionmentioning
confidence: 99%